Ameloblastic fibroma: a series of 10 cases from South America - de Arruda, José Alcides Almeida; Ventura, José Victor Lemos; Barreto, Maria Eduarda Zeraik; Villarroel-Dorrego, Mariana; Peña-Vega, Claudia Patricia; Rodríguez-Mora, Juan Pablo; de Sena, Ana Carolina Velasco Pondé; Cavalcante, Israel Leal; Valle, Isabella Bittencourt do; Andrade, Emanuel Sávio de Souza; et al. (Journal of Oral Diagnosis, 2025)
Objective: Ameloblastic fibroma (AF) is a rare odontogenic tumor composed of ectomesenchymal tissue and epithelial components, without the formation of dental hard tissues. Despite its recognition, data on AF from South America remain limited. This study describes a series of 10 AF cases from Venezuela and Colombia. Methods: Clinicopathological data, radiographic characteristics, and treatment modalities were analyzed descriptively. Results: The series comprised seven (70%) female and three (30%) male patients, with a mean age of 12.9 years. Lesions were predominantly located in the posterior mandible (80%). Radiographic findings revealed radiolucent lesions associated with bone expansion and involvement of adjacent teeth. Treatment modalities included mandibular resection and hemimandibulectomy, accounting for 66.6% of cases. Recurrence was observed in one case (16.7%). Conclusion: This study provides novel data on AF in South America, particularly in pediatric patients, and highlights the need for long-term surveillance and optimized treatment strategies due to the potential for recurrence.